2023
DOI: 10.1021/acs.jpca.2c07349
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Understanding on the Effective Generation of Twisted Intramolecular Charge Transfer by Protonation in Thiazolo[5,4-d]thiazole Derivatives

Abstract: The exploration of the intrinsic relationship between the phototautomerization and photoelectric properties is of great significance for the application of the emerging novel organic materials, such as the (bi)heterocyclic thiazolo [5,4d]thiazole derivatives (TzTz). Here, by introducing the chemicalcontrolling protonation, a barrierless spontaneous rotation movement of the designed TzTz derivative (2,5-diyl-amino-thiazolo[5,4d]thiazole, DA-TzTz) was ensured through the facilitation of the excited-state intramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…According to previous research on ESIPT-capable compounds, the proton transfer process can lead to a radiationless deactivation via a conical intersection (CI) of non-planar nature (in other words, through a so-called twisted intramolecular charge transfer (TICT) state). 134–144 We noticed that the geometries of the S 1 state with an O–H distance constraint greater than 1.8 Å cannot be optimized due to oscillations around a C Ph –C Pym bond connecting the hydroxyphenyl and pyrimidine moieties. Unconstrained geometry optimization of the S 1 state with l (O–H) > 1.8 Å directly leads to a non-planar geometry (near-CI geometry in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous research on ESIPT-capable compounds, the proton transfer process can lead to a radiationless deactivation via a conical intersection (CI) of non-planar nature (in other words, through a so-called twisted intramolecular charge transfer (TICT) state). 134–144 We noticed that the geometries of the S 1 state with an O–H distance constraint greater than 1.8 Å cannot be optimized due to oscillations around a C Ph –C Pym bond connecting the hydroxyphenyl and pyrimidine moieties. Unconstrained geometry optimization of the S 1 state with l (O–H) > 1.8 Å directly leads to a non-planar geometry (near-CI geometry in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…26 Furthermore, due to the energy/ charge transfer between the excited state of the solute molecule and the solvent molecule, the polarity dominantly induced alterations in the uorescence emission wavelength, 27 lifetime, and quantum yield (known as solvatouorochromism) also attract special attention. A recent study shows that ICT character at an excited state for asymmetric thiazolo [5,4-d]thiazole (TTz) [28][29][30] derivatives was strengthened by the solvating effect of a polar solvent, reecting as a decreased quantum yield, an increased lifetime and a bathochromic-shi. As mentioned above, the solvation effect can be studied in depth and promising to be applied to modulate the optical sensing response from either reaction progress or optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…31−33 Typically, the TICT process is triggered by ESIPT through both the lowering of the torsion barrier by the intramolecular hydrogen bonding and the change in the conjugated system brought by the proton transfer process itself. 34,35 Thus, the synergy of these two processes could not only make the torsional configuration more stable but also ensure an efficient electron−hole separation. Accordingly, the unique properties of the ESIPTtriggered TICT process have been widely used in various functional organic materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The deep understanding of intrinsic logical relations between the configurational variation and photochemical properties of the organic sensitizers has attracted considerable research interest, particularly in areas such as fluorescent dyes, fluorescent sensors, and organic luminescence devices. As one of the most fundamental and significant configurational variations caused by the excitation-strengthened hydrogen bonds, the excited-state intramolecular proton transfer (ESIPT) shows various photochemical properties involving the intramolecular charge transfer (ICT) process. The twisted intramolecular charge transfer (TICT) is a unique form of ICT that typically leads to the dissociation of the π-conjugated systems and significant changes in electron density distributions throughout the molecule. The twisting process, which involves the decoupling of the π-systems between the acceptor and the donor units, could lead to a minimal transition dipole strength between the excited and the ground states, resulting in the formation of a stable TICT state . It has been found that the strategy of utilizing the ESIPT-triggered TICT effectively maintains the torsional advantage between the countering fragments by lowering the molecular energy, which is accompanied by the destruction of the π-conjugation systems and the efficient charge transfer, ensuring a complete charge transfer and separation. Typically, the TICT process is triggered by ESIPT through both the lowering of the torsion barrier by the intramolecular hydrogen bonding and the change in the conjugated system brought by the proton transfer process itself. , Thus, the synergy of these two processes could not only make the torsional configuration more stable but also ensure an efficient electron–hole separation. Accordingly, the unique properties of the ESIPT-triggered TICT process have been widely used in various functional organic materials. However, it remains a challenge to extend this strategy to simple and versatile π-conjugated structures consisting of proton donors and acceptors, which is essential to gain insight into the exploration of structural change-related novel sensitizers.…”
Section: Introductionmentioning
confidence: 99%